2020
DOI: 10.1038/s41598-020-74766-7
|View full text |Cite
|
Sign up to set email alerts
|

The silk of gorse spider mite Tetranychus lintearius represents a novel natural source of nanoparticles and biomaterials

Abstract: Spider mites constitute an assemblage of well-known pests in agriculture, but are less known for their ability to spin silk of nanoscale diameters and high Young’s moduli. Here, we characterize silk of the gorse spider mite Tetranychus lintearius, which produces copious amounts of silk with nano-dimensions. We determined biophysical characteristics of the silk fibres and manufactured nanoparticles and biofilm derived from native silk. We determined silk structure using attenuated total reflectance Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…This includes the development of new methods based on RNAi to control mites [88] that may function across species. Furthermore, the development of new materials derived from mites, such as spider mite silk and nanoparticles developed from the silk [89], will expand the utilization of mite-derived materials in biomedicine. Thus, research on mites is entering a dynamic period where these organisms with sequenced genomes will provide novel tools for their control as well as the application of mite-derived products in different, non-traditional fields.…”
Section: Studies Of Mites At the Molecular Levelmentioning
confidence: 99%
“…This includes the development of new methods based on RNAi to control mites [88] that may function across species. Furthermore, the development of new materials derived from mites, such as spider mite silk and nanoparticles developed from the silk [89], will expand the utilization of mite-derived materials in biomedicine. Thus, research on mites is entering a dynamic period where these organisms with sequenced genomes will provide novel tools for their control as well as the application of mite-derived products in different, non-traditional fields.…”
Section: Studies Of Mites At the Molecular Levelmentioning
confidence: 99%
“…Beyond spiders, other arachnids can produce silks. The silk fibers of the spider mite Tetranychus urticae, for example, have diameters on the nanometer scale, representing the thinnest natural silk fiber produced by arthropods (Lozano-Peŕez et al, 2020). Combined with a Young's modulus almost double that of spider Trichonephila clavipes silk, the spider mite silks show great potential in pharmacological and biomedical application (Lozano-Peŕez et al, 2020).…”
Section: Grand Challenge 3: Interpret Arachnid Trait Evolution Throug...mentioning
confidence: 99%
“…[164] Lozano-Perez et al reported that spider mite silk nanoparticles enter the cell cytoplasm and support the in vitro mammalian cell growth. [165] Besides, spider silk offers quick adherence and culture coverage making it a great biomaterial for scaffold design. [166] Silkworm cocoon is a promising wound dressing as its protective function resembles that of the human skin.…”
Section: Proteinsmentioning
confidence: 99%
“…reported that spider mite silk nanoparticles enter the cell cytoplasm and support the in vitro mammalian cell growth. [ 165 ] Besides, spider silk offers quick adherence and culture coverage making it a great biomaterial for scaffold design. [ 166 ]…”
Section: Biomaterials’ Composition Properties and Applicationsmentioning
confidence: 99%